ANALISIS PENERAPAN SANKSI ADMINISTRASI PADA PELAKSANAAN PENGELOLAAN LIMBAH PADA RUMAH SAKIT UMUM RADEN MATTAHER JAMBI - Raharja, Ivan Fauzani (Solusi, 2018)
Medical waste is very important to manage properly, this is because medical waste belongs to the category of hazardous and toxic waste. Some of the medical waste is included in the category of hazardous waste and part of it is infectious. In relation to RSUD Raden Mattaher Jambi waste management problem, the ministry of environment giving black label in 2014 means that its waste management is very bad and it can affect the imposition of administrative sanction which will be accepted by RSUD Raden Mattaher Jambi. According to Article 198 of Government Regulation Number 101 Year 2014 on the Management of Hazardous and Toxic Wastes "Any Person who produces B3 Waste, B3 Waste Collector, B3 Waste Carrier, B3 Waste Users, B3 Waste Processors and / or B3 Waste Landmakers conducting Environmental Pollution and / or Destruction of Compulsory Environment implement: a. Environmental Pollution and / or Environmental Degradation; and b. Environmental Function Recovery. Given these laws and regulations, hospital waste management should be guided by applicable regulations. if it is not implemented then the government has the right to impose administrative sanctions on the matter either in the form of revocation of temporary permit or other form which has been determined.